Pengembangan Lembar Kerja Peserta Didik Untuk Meningkatkan Penguasaan Konsep dan Keterampilan Pemecahan Masalah Peserta Didik - Yusrizal Yusrizal; Evendi Evendi; Elisa Elisa; S. Ilyas; Riska Lisanti (Jurnal Penelitian Pendidikan IPA, 2022)
Physics learning is learning related to natural phenomena, not only in the form of memorization but more demanding on understanding, applications and concepts that are scientifically integrated in mastering concepts and problem solving skills. The purpose of this research is to develop student worksheets based on scientific approach to improve students' mastery of concepts and problem solving skills. The method used in this research is research and development (R&D) which refers to the ADDIE development model. Student worksheets implementation design uses One Group Pretest-Posttest Design. The instruments used in this study were student worksheets assessment sheets, test questions for mastery of concepts and problem solving skills, student response questionnaires and teacher response questionnaires. Mastery of concepts and problem solving skills of students were analyzed using the N-Gain test to see the improvement before and after the implementation of student worksheets based on the Scientific approach. The results of the feasibility test in terms of the feasibility aspects of content, presentation and language obtained a percentage of 96.66% indicating that the student worksheets based on the Scientific approach to improve mastery of concepts and problem solving skills is very feasible to use. The results of the implementation of the student worksheets based on the Scientific approach can improve the mastery of concepts and problem solving skills of students which is marked by an increase in the pretest-posttest scores based on the results of the N-Gain test which shows the numbers 0.68 and 0.69 are in the medium categories. Teachers and students responded with a very positive category to SW based on a Scientific approach which was shown by figures of 3.31% for teacher responses and 105.38% for student responses